The effectiveness of promotion activities at MPH Bookstores BB Plaza / Siti Noorazian Ismail - Ismail, Siti Noorazian (Faculty of Business and Management, 2008)
This study focuses on "The effectiveness of Promotion Activities at MPH Bookstores BB Plaza". This objective is to identify the most effective promotion activities made by MPH Bookstores BB Plaza, to identify relationship between sales promotion and the promotion effectiveness a MPH Bookstores BB Plaza, to identify relationship between public relation and the promotion effectiveness at MPH Bookstores BB Plaza, and to identify relationship between advertising and the promotion effectiveness at MPH Bookstores BB Plaza. The sampling technique that has been used was the nonprobability sampling where 50 respondents were chosen to answer the questionnaire. The result of the finding shows that the promotion activities through advertising were given greatest exposure on MPH Bookstores BB Plaza.